Influencing Factors of the Distribution Accuracy and the Optimal Parameters of a Pneumatic Fertilization Distributor in a Fertilizer Applicator - Wensheng Yuan; Changying Ji; Zhiyuan Liu; Chengqian Jin; Yugang Feng (Agronomy, 2022)
A pneumatic fertilization distributor used for fertilizing in a fertilizer applicator is a key component of the applicator. The parameters of a pneumatic fertilization distributor affect the uniformity and accuracy of the fertilization of a fertilizer applicator. To obtain the optimal design parameters of a pneumatic fertilization distributor, a fluidstructure coupling simulation test and a bench test were carried out in the Intelligent Agricultural Machinery Laboratory of the Nanjing Institute of Agricultural Mechanization from March 2021 to July 2022. The curvature–diameter ratios of the elbow, bellow length, and air velocity were selected as the experimental factors, and the variation coefficient of the fertilizer discharge at each discharge outlet within 0.5–3 s was selected as the experimental index. A five-level quadratic regression orthogonal rotation combined test was carried out. The results showed that: (1) all three factors had a significant impact on the uniformity of the fertilizer discharge. The reasonable ranges of the curvature–diameter ratio, bellow length, and air velocity were 0.5–1.5, 350–550 mm, and 25–35 m/s, respectively. (2) The order of the influence of the three factors on the uniformity of the fertilizer discharge in descending order was as follows: the curvature–diameter ratio of the elbow, the bellow length, and the air velocity. When the bellow length was 460 mm, the curvature–diameter ratio was 0.6, and the inlet air velocity was 28 m/s. The uniformity of the fertilizer discharge was optimal. A pneumatic conveying system was redesigned according to the optimal parameters, and a bench test was carried out. The results showed that at different speeds, the coefficient of variation of each row’s displacement was not greater than 5%, and the simulation test results were consistent with the bench test results.